2013
DOI: 10.1074/jbc.m113.479964
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity of the Peptidyl-Prolyl Isomerase Domain from the Histone Chaperone Fpr4 toward Histone H3 Proline Isomerization

Abstract: Background:The yeast histone chaperone Fpr4 harbors a peptidyl-prolyl isomerase domain of the FK506-binding protein (FKBP) family. Results: Catalytic efficiency toward three peptides from histone H3 relates to residues flanking the central proline. Conclusion: Substrate residues C-terminal to the proline dictate isomerase activity by Fpr4. Significance: The findings reveal new molecular details of substrate peptide recognition by the peptidyl-prolyl isomerase domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The C-terminal PPI of FKBP39, which has a pI of 10, did not show in our hands any interaction with histones in vitro . On the other hand, the PPI domain of Fpr4, which is similarly positively charged, does turn over H3 histone peptides and has a charge-compatible active site [12,14] . In order to establish which part of FKBP39 is responsible for the abovementioned interactions, two further protein A pull-down experiments were carried out: one with the amino-terminal half and the other one with the carboxy-terminal half of the protein (including the PPI domain).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal PPI of FKBP39, which has a pI of 10, did not show in our hands any interaction with histones in vitro . On the other hand, the PPI domain of Fpr4, which is similarly positively charged, does turn over H3 histone peptides and has a charge-compatible active site [12,14] . In order to establish which part of FKBP39 is responsible for the abovementioned interactions, two further protein A pull-down experiments were carried out: one with the amino-terminal half and the other one with the carboxy-terminal half of the protein (including the PPI domain).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps due to its unique role, nucleoplasmin's similarity to a group of proteins implicated in chromatin regulation, such as the plant type 2 histone deacetylases, or HD-tuins [7–11] , and the yeast Fpr3 and Fpr4 proteins [12–14] , has never been noticed. The family's defining feature is an N-terminal domain of unknown structure with a signature motif of conserved hydrophobic and two potentially catalytic residues—a histidine and an aspartate [15] .…”
Section: Introductionmentioning
confidence: 99%
“…While there are good examples to support this model ( 9 , 10 , 96 , 97 ), a growing body of literature demonstrates that these proteins also have non-catalytic impacts on biological processes, presumably via direct binding events ( 27 , 28 , 98 , 99 ). For example, we recently showed that the FKBP domain of yeast Fpr4, which can target histone prolines ( 10 , 100 ) could also affect chromatin fiber self-association independently of catalytic function ( 101 ). This illustrates that targets of catalytic action may reside close to or within binding partners of FKBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Given these findings, histone H1 may be a target for prolyl isomerization by FKBP25 in the regulation of DNA repair. If true, this would imply that FKBP25's catalytic activity might promote HR through remodeling the chromatin environment, which would be similar to the histone-binding/chromatin targets and recombination checkpoint functions of the orthologous nuclear FKBPs in yeast (Hochwagen et al 2005;Nelson et al 2006;Macqueen and Roeder 2009;Monneau et al 2013;Ohkuni et al 2014;Edlich-Muth et al 2015;Leung et al 2017). While further work is required, a role in DNA damage repair may explain FKBP25's, so far inexplicable, association with chromatin.…”
Section: Discussionmentioning
confidence: 99%